Locating Resilience in Art: An Autoethnographic Study - Granovsky, Melissa (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2024)
This autoethnography aims to explore how resilience supported me in navigating identity confusion after discovering my Métis heritage at 19, coinciding with meeting my father for the first time. The data sources I analyzed were reflective journal entries, photographs, a self-written letter, and three art pieces to track my progress. Informing this process were feminist theory and Indigenous research methodologies, ensuring it was approached from a decolonized and feminist perspective. My key finding was that resilience-building strategies must be intentional and ongoing to work effectively. In addition to personal resilience-raising capacities, a network of support, positive self-talk, self-love, critical reflection, and trauma-informed care were essential to sustain resilience through adversity. While short-term resilience can be maintained independently, sustaining resilience over the long term necessitates interdependence, collaboration, and structural changes at a broader, systemic level.